Triple‐marker immunohistochemical assessment of muscle‐invasive bladder cancer: Is there prognostic significance?. Issue 2 (4th February 2021) - Labban, Muhieddine; Najdi, Jad; Mukherji, Deborah; Abou‐Kheir, Wassim; Tabbarah, Abeer; El‐Hajj, Albert
Abstract: Background: Bladder cancer is the ninth most common cancer worldwide, and the third most common cancer in Lebanon. Immunohistochemistry (IHC) has been used to stratify muscle‐invasive bladder cancer (MIBC) into different subtypes. However, to our knowledge, there exists no study that investigates the use of this low‐cost technique to predict prognosis in bladder cancer patients in our region. Aim: To examine the feasibility of low‐cost triple‐marker IHC assessment for MIBC subtyping in order to predict patients' survival and cisplatin sensitivity. Methods and results: We collected the specimens of deceased patients diagnosed with MIBC on pathology at our institution. For each case, tumor tissue blocks were retrieved and stained for hematoxylin and eosin in addition to three molecular markers by IHC: cytokeratin 5/6, cytokeratin 14 staining basal BC, and GATA3 staining luminal BC. A cut‐off of ≥20% was set as positive. Kaplan‐Meier curves were built, factored by BC subtype, to predict overall survival (OS), disease‐specific survival (DSS), and progression‐free survival (PFS). Hazard ratios in Cox regression were also created accounting for oncological factors and BC subtype. We categorized specimens as either luminal (GATA3 positive only) (n = 21; 56.7%) or as double‐positive (GATA3 and basal cytokeratin 5/6 or cytokeratin 14 positive) (n = 16; 43.3%). The overall median survival was similar between the two categories (27.0 ± 4.82 months). Numbers favored luminal disease for PFS (Breslow P = .032). After adjusting for covariates, luminal molecular expression predicted PFS (0.28; [0.09‐0.94]). Yet, the Cox model was not able to identify any predictors of OS or DSS. Conclusion: Specimens enriched with only a luminal molecular profile were more likely to exhibit cisplatin sensitivity. Despite the absence of guidelines recommending the utilization of molecular profiling in clinic practice, triple‐marker IHC could serve as a potential low‐cost prognostic indicator to identify patients at high risk of progression.